Adherence to Anticoagulation Interruption Guidelines in Patients with Atrial Fibrillation. (11th March 2023) - Siddique, Mujtaba; Butt, Asif; Sultan, Nazeem; Ahmed, Farhat; Shuaib, Ashfaq
ABSTRACT: Introduction: Annually, 15% of patients who receive oral anticoagulation require interruption for surgery or an invasive procedure. This study evaluates the adherence of patients with atrial fibrillation with a history of stroke or transient ischemic attack to the Thrombosis Canada Perioperative guidelines for the discontinuation and reinitiation of anticoagulation treatment. Methods: We collected data from a prospective patient survey at the Stroke Prevention Clinic in the University of Alberta hospital. Patients' charts were reviewed from the electronic medical records, and adherence was looked at according to the Thrombosis Canada Perioperative guidelines for the interruption of anticoagulants. Results: During the study period (2016–2019), there were 509 patients surveyed. Anticoagulation treatment was interrupted in 150 patients with 98 interrupted for surgical or invasive procedures. The interruption was adherent to guidelines in only 29 (29.6%) of patients and inappropriate or nonadherent in 69 (70.4%) patients. There were seven ischemic strokes recorded during the period of interruption. The proportion of strokes was higher in patients whose anticoagulation interruption was longer than what the guidelines recommended (6/61 or 9.8%) when compared to those who adhered to recommended perioperative anticoagulation guidelines (1/29 or 3.4%). Conclusion: Our results indicate that significant discrepancy with following the recommended perioperative anticoagulation guidelines is common in real-life practice. Delay in re-anticoagulation may increase the risk of complications.